(untitled) (INTERNATIONAL SCIENCE REVIEWS. SOCIAL SCIENCES SERIES, 2024)
Abstract. Women’s social entrepreneurship sheds light on the barriers, challenges and opportunities faced by women in business and leadership positions. Women’s social entrepreneurship addresses pressing social and environmental issues, promoting positive change in communities. Research in this area highlights the unique approaches, innovative solutions, and social impact outcomes achieved by women-led social enterprises, inspiring others and promoting social entrepreneurship as a whole. The article considers the distinctive features of women’s social entrepreneurship. The author has studied the experience of foreign countries where women’s social entrepreneurship is developed, examples of famous social projects led by women are given. SWOT-analysis and PEST-analysis of the development of women’s social entrepreneurship in Kazakhstan are carried out. The author of the article outlined the problems faced by social entrepreneurs in Kazakhstan, especially women entrepreneurs.